From Warriors to Soldiers: Regularising Military Logistics and the Emergence of Military Medicine. The Case of the Armatoles (c. 1800–1831) - Barlagiannis, Athanasios (Historein, 2022)
The article explores the coincidence of military and medical reforms in the Ottoman Empire, which occurred around the turn of the nineteenth century, by connecting both developments to the question of the steady flow of supplies to military camps. The intention to organise a standing army to replace the military force of local warriors, like the armatoles in Rumelia, presupposed the monopolisation of sources of power and the regularisation of logistics. As a result, free warriors became obedient soldiers as they were progressively alienated from the means of warfare. Physicians and surgeons were integrated at one point into the armies of the empire in order to successfully organise their logistics and to expand the definition of the means of warfare to include the soldier’s body – intensifying thus the forces of military discipline. Military medicine was the byproduct of a transformation process that the armatoles were already undergoing before the 1821 Greek Revolution and that Governor Ioannis Kapodistrias (1828–1831) concluded. Ultimately, the article opens up the discussion about the political, medical, cultural and military implications of the transition from the empire to the state and of the emergence in this context of military medicine.